1996
DOI: 10.1523/jneurosci.16-14-04501.1996
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Superior Temporal Cortex Lesions on the Processing and Retention of Auditory Information in Monkeys (Cebus apella)

Abstract: Three monkeys with extensive preoperative training on visual and auditory memory tasks (delayed matching-to-sample), an auditory pattern-discrimination task, and a visual serial-order task, received bilateral lesions of the superior temporal (ST) cortex in two stages, with testing after each lesion. Unilateral ST cortex lesions resulted in only moderate auditory memory impairments, whereas bilateral ST cortex lesions resulted in severe auditory memory impairments. The bilateral ST cortex lesions also resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 118 publications
4
46
0
1
Order By: Relevance
“…We next proceeded to test the hypothesis that this ventrolateral prefrontal region may be interacting functionally with the auditory temporal region that is known to play a role in the encoding and retention of auditory stimuli (32,33) and the parietal region that processes spatial information (34)(35)(36). We therefore examined whether there was a significant change in functional connectivity between the midventrolateral prefrontal cortex and the secondary auditory temporal and the posterior parietal region during the active retrieval compared with the recognition control trials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next proceeded to test the hypothesis that this ventrolateral prefrontal region may be interacting functionally with the auditory temporal region that is known to play a role in the encoding and retention of auditory stimuli (32,33) and the parietal region that processes spatial information (34)(35)(36). We therefore examined whether there was a significant change in functional connectivity between the midventrolateral prefrontal cortex and the secondary auditory temporal and the posterior parietal region during the active retrieval compared with the recognition control trials.…”
Section: Resultsmentioning
confidence: 99%
“…There are considerable anatomical data that the midventrolateral prefrontal cortex (and particularly area 45) is extensively connected with the superior temporal gyrus and the nearby dorsal bank of the superior temporal sulcus (through the extreme capsule and the arcuate fasciculus) and also with the inferior parietal lobule (area PG) (via the second branch of the superior longitudinal fasciculus) (14, 16-18, 20, 37). The superior temporal region of the primate brain is critical for the encoding and short-term maintenance of auditory information (32,33,38), whereas the caudal superior temporal gyrus and the adjacent parabelt region in the caudal superior temporal sulcus entering the inferior parietal lobule are involved in the spatial aspects of auditory coding (34,36). Indeed, a recent study using transcranial magnetic stimulation has shown that the caudal part of the superior temporal gyrus, close to the inferior parietal lobule, is involved in auditory localization to a greater extent than the more rostral temporal region (39).…”
Section: Discussionmentioning
confidence: 99%
“…This retroactive interference effect in audition seems to be extremely powerful. Prior studies of auditory memory in monkeys tested with nonserial DMS have shown forgetting thresholds (75% correct responses) of up to 30 s in the absence of intervening stimuli, whether the studies used trial-unique stimuli (12) or a set of only two tones (20).…”
Section: Discussionmentioning
confidence: 99%
“…S1). Because of the known difficulty monkeys have in acquiring and applying the rule for auditory DMS (12,(18)(19)(20)(21)(22), we simplified task requirements by requiring the animal to (i) remember a single sample stimulus for 1 s, and (ii) respond at test to an identical match stimulus and withhold responding to a nonmatch that, importantly, always belonged to a stimulus category other than the sample's category. The only To whom correspondence may be addressed.…”
mentioning
confidence: 99%
“…It is possible that disruption of local cortical activity alone could suppress hearing, although it is generally agreed that in humans (Tramo et al, 2002;Kaga et al, 2000;Hausler and Levine, 2000;Penfield and Perot, 1963) and in laboratory animals (Heffner and Heffner, 1986;Heffner, 1997;Colombo et al,1996;Whitfield et al, 1978) that unilateral destruction of auditory cortex of the STG does not result in deafness. More likely, hearing suppression is the result of activating corticofugal efferent pathways that project to auditory thalamic, midbrain and brainstem structures, and possibly the cochlea (Hazama et al, 2004;He, 2003;Jacomme et al, 2003, Suga andPandya et al, 1994;Weedman and Ryugo, 1996a,b).…”
Section: Discussionmentioning
confidence: 99%